Exploring the relationship between CEO characteristics and performance - Garcia-Blandon, Josep; Argilés-Bosch, Josep M.; Ravenda, Diego (Journal of Business Economics and Management, 2019)
This article examines the relationship between CEO characteristics and firm performance with a sample formed by the best performing CEOs in the world according to Harvard Business Review. The empirical analysis is based on descriptive statistics techniques and studies the universe of CEOs included in the 2016 ranking “The Best-Performing CEOs in the World” released by Harvard Business Review. Moreover, it addresses performance at various levels: financial performance, environmental, social and governance performance (ESG) and overall performance. The findings of the study show: 1) a strongly negative association between financial and ESG performance; 2) outsider CEOs outperform insider CEOs in overall performance; 3) CEOs with engineering degrees show significantly higher ESG performance; 4) CEOs with longer tenures in the firm present stronger financial performance though weaker ESG performance; and 5) the CEO’s country of origin emerges as an important driver to explain the different types of performance. Results in this field contradict the conventional wisdom of Anglo-Saxon CEOs as the best performers CEOs.